A dormant resource for genome size estimation in ferns: C‐value inference of the Ophioglossaceae using herbarium specimen spores. (7th December 2021) - Kuo, Li‐Yaung; Tang, Sheng Kai; Kao, Tzu‐Tong; Ebihara, Atsushi; Fawcett, Susan; Hsiao, Min‐Chien; Shinohara, Wataru; Dauphin, Benjamin
Abstract: Premise: The great variation of genome size (C‐value) across land plants is linked to various adaptative features. Flow cytometry (FCM), the standard approach to estimating C‐values, relies mostly on fresh materials, performing poorly when used with herbarium materials. No fern C‐value reports have been derived from herbarium specimens; however, the herbarium spores of some ferns remain highly viable for decades and are thus promising for further investigation. To explore this possibility, we evaluated herbarium spore collections of Ophioglossaceae ferns using FCM. Methods: Flow cytometry was conducted on 24 spore samples, representing eight of the 12 genera of the Ophioglossaceae, using specimens ranging in age from 2.6 to 111 years obtained from five herbaria. Results: Regardless of the genus or the source herbarium, high‐quality C‐value data were generated from 17 samples, with the oldest being 26 years old. Estimates of the C‐values from sporophytic tissues of known ploidy did not reveal any evidence of apomixis for the species surveyed here. We also detected a pronounced genome downsizing in Sceptridium polyploids. Discussion: The recent success of FCM for C‐value estimation using spores provides a much more convenient method of utilizing "dry" refrigerated materials. We demonstrate here that herbarium spores of some ferns are also promising for this use, even for older specimens.